Inhaled GM-CSF administered during ongoing pneumovirus infection alters myeloid and CD8 T cell immunity without affecting disease outcome - Debeuf, Nincy; Deckers, Julie; Lameire, Sahine; Bosteels, Cedric; Hammad, Hamida; Lambrecht, Bart N. (Frontiers in Immunology, 2024)
Granulocyte-macrophage colony stimulating factor (GM-CSF) is a pleiotropic cytokine, able to promote both myelopoiesis and activation of immune cells. Particularly in the lung, GM-CSF plays an important homeostatic role in the development and maintenance of alveolar macrophages, and is therefore considered to play a role in respiratory virus infections such as influenza and SARS-CoV-2, although the benefits of GM-CSF treatment in clinical studies remain inconclusive. To address this, we tested inhaled GM-CSF treatment in the Pneumonia Virus of Mice (PVM) mouse model. Our findings show that local GM-CSF therapy during PVM disease increased local neutrophilia and monocyte-derived cell influx, but diminished CD8 + T cells responses. Despite this, the observed effects on T cells and myeloid cells did not result in an altered clinical outcome during PVM infection. We conclude that inhaled GM-CSF therapy cannot be considered as a universal protective therapy in respiratory virus infections.